Exploring species composition and population dynamics of thrips (Thysanoptera: Thripidae) in peanut crops in Argentina - De Breuil, Soledad; Giudici, Albano Cesar; La Rossa, Francisco Ruben; Baldessari, Jorge Javier; Bejerman, Nicolas Esteban; Giolitti, Fabian; Lenardon, Sergio Luis (Springer, 2021)
Thrips (Thysanoptera: Thripidae) are major pests of peanut (Arachis hypogaea L.). They cause feeding damage and indirect injuries transmitting plant viruses. In Argentina, peanut is commonly affected by thrips. The crop also is infected by groundnut ringspot orthotospovirus, a virus transmitted by thrips vectors. However, in the country, information about thrips in peanut is very scarce. A 3-yr study was conducted to characterize the species composition and thrips population dynamics in the main peanut-producing area in Argentina. Frankliniella schultzei (Trybom), followed by Caliothrips phaseoli (Hood) were the most abundant species. Together the two species accounted for ~ 95-99 % of the total adult thrips captured in each season. Significant different abundances were observed among these two thrips species throughout each peanut growing season. Nevertheless, the temporal dynamics of F. schultzei and C. phaseoli showed a similar trend in the three study years. In general, the colonization by F. schultzei started in late December and their population increased from the second half of January peaking around the first half of February. The highest densities of F. schultzei occurred simultaneously in foliage and flowers during the warmer months of the year.